2017
DOI: 10.1177/1099636217697495
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent in vibration analysis of magnetostrictive sandwich composite micro-plate in magnetic field using modified couple stress theory

Abstract: In the present study, free vibration of magnetostrictive sandwich composite micro plate with magnetostrictive core and composite face sheets are investigated. The modified couple stress theory is taken into account so as to consider the small scale effects. The surrounding elastic medium is simulated as visco-Pasternak foundation to study the effects of both damping and shear effects. Using energy method, Hamilton’s principle and first-order shear deformation theory, the governing equations of motion and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is an attractive substitute for piezoelectric ceramic materials, and the giant magnetostrictive sensor has attracted much attention [ 21 ]. Ghorbanpour Arani et al [ 22 ] studied the free vibration of magnetostrictive sandwich composite microplates with magnetostrictive cores and composite panels and found that the angle between the magnetic field and the composite fiber plays a key role in the dimensionless frequency of microplates. This can be used in the design of sensors and provide ideas for the vibration response control of systems in the aerospace industry.…”
Section: Introductionmentioning
confidence: 99%
“…It is an attractive substitute for piezoelectric ceramic materials, and the giant magnetostrictive sensor has attracted much attention [ 21 ]. Ghorbanpour Arani et al [ 22 ] studied the free vibration of magnetostrictive sandwich composite microplates with magnetostrictive cores and composite panels and found that the angle between the magnetic field and the composite fiber plays a key role in the dimensionless frequency of microplates. This can be used in the design of sensors and provide ideas for the vibration response control of systems in the aerospace industry.…”
Section: Introductionmentioning
confidence: 99%
“…The sandwich plate was made from a magnetostrictive core and two composite faces. Ghorbanpour Arani et al (2017b) investigated the vibration of magnetostrictive microplates, which was located on the viscoelastic foundation based on the FSDT. They found magnetic field has a significant effect on the behavior of the magnetostrictive plate.…”
Section: Introductionmentioning
confidence: 99%